Estimate the Prevalence of Fatty Liver in Overweight and Obese Children in Ilam - Gholamreza Kalvandi; Reza Najafi; Kourosh Sayehmiri; Salah Saki (Indian Journal of Forensic Medicine & Toxicology, 2022)
Introduction: Obesity worldwide is considered as the single largest cause of chronic illness. The children of thepresent generation are the only people throughout history who die because of problems with overweight beforetheir parents. Obese children are prone to fatty liver disease. Fatty liver is one of the chronic liver disorders thatis associated with lipid accumulation in hepatocytes. The aim of this study was to estimate the prevalence of fattyliver in overweight and obese children in Ilam and to investigate some of its possible causes, in order to considerthe need for planning for educational interventions for behavioral change.Method: This cross-sectional study was carried out in Imam Khomeini Hospital, Ilam, in 2017, and among 106children aged 6-18 years who were referred to the center for evaluation, a randomized sampling was performedand divided into two groups of overweight and obese based on their BMI.Conclusion: Regarding the relatively high prevalence of non-alcoholic fatty liver disease in school-age children,and especially in adolescents, the need to educate parents and their children for proper nutrition and daily physicalactivity with the correct method is still felt.